Toward a sustainable research agenda on food eco-labelling in the business and management research domain - Valeska V. Geldres-Weiss; Carolina Nicolas; Nathaniel P. Massa (European Journal of Management and Business Economics (EJM&BE), 2024)
Purpose - This study aims to critically review the research on food eco-labels to identify research gaps and recommend future research directions in business and management. Design/methodology/approach A hybrid integrated review combines bibliometric analysis with an in-depth framework-based study of theory-context-characteristics-methodology (TCCM) and reviews quality research published over 21 years between 2002 and 2022. Findings We identify key research themes and the knowledge structure of food eco-label research. Future researchers should explore food eco-label dynamics and phenomena in areas related to consumer behaviour, information, consumer knowledge, environmental concerns, trust, packaging and willingness-to-pay as antecedent factors. Research limitations/implications This review contributes to the business and management literature by quantifying existing research and consolidating its evolution. The articles were sourced from the established Web of Science (WoS) database. Other databases should be included in future reviews. We also focus on research published in business and management. Further studies could include research beyond such specialised domains. Practical implications Consumers need more information on the objectives and meaning of food eco-labels. The dissemination of knowledge on eco-labels, as well as effective communication and information on eco-labels, are relevant to future research issues. Social implications The knowledge derived from this research holds significant potential in shaping policies and devising tools aimed at reducing the carbon footprint linked to food production and consumption. Considering the substantial impact of these activities on our planet's carbon footprint, addressing food security and sustainability emerges as a crucial concern for humanity. Recognising the importance of eco-label communication and information becomes particularly pertinent for future generations, who stand to bear the most substantial impact of climate change and sustainable development. These generations are also more inclined toward embracing and implementing sustainable practices. Originality/value There are no comprehensive, integrated reviews exploring the methods, variables and constructs used in studies on food eco-labels based on all articles published in WoS journals in the business and management domains. This is the first comprehensive literature review using a hybrid approach (bibliometric review with TCCM framework) in the field of food eco-label research.
Keywords: 650; Bibliometric analysis; Eco-label; Food; Marketing; Sustainability; TCCM